Identifikasi Ruang Komunal pada Permukiman Padat Penduduk - Sherly Defannya Serdani; Verry Damayanti (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Cicadas Subdistrict is one of the densely populated in the center of Bandung City. One of the RW's is a TNI AD housing complex with limited access. Limited land causes this area to not have sufficient communal space as a means of community interaction. The purpose of this research is to identify communal spaces in dense settlements in Cicadas Subdistrict. This study uses an empirical and spatial approach that is used to get an overview of current conditions in identifying communal spaces in densely populated settlements in Cicadas Subdistrict. The analysis in this study uses empirical quantitative analysis to determine the location of communal and spatial spaces by mapping the distribution of communal spaces using ArcGIS software. To obtain data, a primary survey and a secondary survey were carried out, from the results of the identification of the distribution of communal spaces in Cicadas Subdistict, it is known that communal spaces in Cicadas Subdistict consist of 7 RW halls, 1 Buruan Sae, 13 street points/alleys, 1 subdistrict office, 4 fields, 1 madrasah, 11 mosques, 3 security posts, 2 posts, 3 posyandu, 1 resident's house, 2 parks, and 2 stalls spread across almost all RW's. The majority of these communal spaces are communal spaces that are not planned as communal spaces such as houses, alleys, fields and parks that are not functioning properly, especially places that are very close to residential areas with informal activities and a very frequent frequency. The limited land available also gives rise to unique communal spaces, such as "Hati - Hati". Abstrak. Kelurahan Cicadas merupakan salah satu kelurahan padat penduduk yang berada di tengah Kota Bandung. Salah satu RW di Kelurahan ini merupakan komplek perumahan TNI AD yang aksesnya terbatas. Terbatasnya lahan menjadikan kawasan ini tidak memiliki cukup ruang komunal sebagai sarana interaksi masyarakat. Tujuan penelitian ini ialah mengidentifikasi ruang-ruang komunal pada permukiman padat di Kelurahan Cicadas. Penelitian ini menggunakan pendekatan empiris dan spasial yang digunakan untuk mendapatkan gambaran kondisi saat ini dalam mengidentifikasi ruang-ruang komunal pada permukiman padat penduduk Kelurahan Cicadas. Adapun analisis pada penelitian ini menggunakan analisis kuantitatif empiris untuk mengetahui letak ruang-ruang komunal dan spasial dengan memetakan sebaran ruang-ruang komunal menggunakan software ArcGIS. Untuk memperoleh data dilakukan dengan survey primer dan survey sekunder. Dari hasil identifikasi sebaran ruang komunal di Kelurahan Cicadas, didapatkan hasil bahwa ruang komunal di Kelurahan Cicadas terdiri dari 7 balai RW, 1 Buruan Sae, 13 titik jalan/gang, 1 kantor kelurahan, 4 lapangan, 1 madrasah, 11 masjid, 3 pos kamling, 2 pos merokok, 3 posyandu, 1 rumah warga, 2 taman, dan 2 warung yang tersebar hampir di seluruh RW Kelurahan Cicadas. Mayoritas ruang-ruang komunal tersebut merupakan ruang-ruang komunal yang tidak direncanakan sebagai ruang komunal seperti rumah warga, gang, lapangan dan taman yang tidak difungsikan sebagaimana mestinya, terutama tempat-tempat yang sangat dekat dengan hunian dengan sifat kegiatan informal dan dengan frekuensi yang sangat sering. Keterbatasan lahan yang ada juga memunculkan ruang – ruang komunal yang unik, seperti “Hati – Hati”.